The effect of granularity on surface roughness and contact angle in wood sanding process. (1st December 2020) - Luo, Bin; Zhang, Jian; Bao, Xue; Liu, Hongguang; Li, Li
Graphical abstract: Highlights: A new calibration method of reference plane has been developed to Sa measurement. The effect of granularity on surface roughness and contact angle has been analyzed. GRA was used to study the relationship between surface roughness and contact angle. Abstract: Sanding is a common machining method to obtain good surface quality. The 2D surface roughness Ra presents high error due to the biological structure of wood materials. In this study, a new calibration method of reference plane is proposed to measure 3D surface roughness Sa, especially for large format panels. Besides, the effects of G (granularity) on Ra, Sa and θ (equilibrium contact angle) are investigated on Korean pine ( Pinus koraiensis Sieb. Et Zucc. ), JATOBA ( Hymenaea cunrbaril L. ) and medium density fiberboard ( MDF ) respectively. The experimental results show the standard deviations of Sa are much lower than that of Ra . As G increased, the variation of Ra, Sa and θ of Korean pine and JATOBA are distinct from MDF . The results of Grey Relevancy Degree ( GRD ) indicate MDF shows an obscure correlation between Sa and θ . The correlation between Sa and θ for Korean pine is the highest.